2016
DOI: 10.1016/j.clsc.2016.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Unresectable Cutaneous Squamous Cell Carcinoma of the Forehead With MLH1 Mutation Showing Dramatic Response to Programmed Cell Death Protein 1 Inhibitor Therapy

Abstract: Treatment of refractory, unresectable cutaneous squamous cell carcinoma presents a great challenge in head and neck oncology with poor prognosis. Prior case reports have shown off-label pembrolizumab, a programed cell death receptor antagonist, can be effective in unresectable cutaneous squamous cell carcinoma. Furthermore, prior reports have suggested enhanced efficacy when high mutational burden is present. In this study we present a severe case of unresectable cutaneous squamous cell carcinoma invading the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 15 publications
0
15
0
1
Order By: Relevance
“…In the absence of cancer, the interaction between lymphocytic PD‐1 and PD‐L1 expressing cells appropriately inhibits T‐cell activation to prevent autoimmunity. The high mutational burden of cSCCs theoretically renders the tumor immunogenic and susceptible to the antitumor T‐cell response . However, PD‐L1 expression in the tumor microenvironment by tumor cells or immune cells suppresses this immune response, preventing host elimination of the cancerous cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of cancer, the interaction between lymphocytic PD‐1 and PD‐L1 expressing cells appropriately inhibits T‐cell activation to prevent autoimmunity. The high mutational burden of cSCCs theoretically renders the tumor immunogenic and susceptible to the antitumor T‐cell response . However, PD‐L1 expression in the tumor microenvironment by tumor cells or immune cells suppresses this immune response, preventing host elimination of the cancerous cells.…”
Section: Discussionmentioning
confidence: 99%
“…Pembrolizumab is a programmed cell death protein 1 (PD‐1) antagonist approved by the Food and Drug Administration for advanced or unresectable melanoma, non‐small‐cell lung cancer, and head and neck squamous cell carcinoma, among others. Prior case reports detail the effective use of off‐label pembrolizumab to treat unresectable cSCC . A phase II trial is currently evaluating the efficacy of pembrolizumab in adults with recurrent or metastatic cSCC .…”
Section: Introductionmentioning
confidence: 99%
“…Recommended doses are 3 mg for kilograms of weight every 3 weeks as intravenous (iv) infusion for a period of 30 minutes. Among the different PD-1 inhibitors, the number of patients treated is the widest, about 28 reported in the literature (Assam et al, 2016;Borradori et al, 2016;Chang et al, 2016;Degache et al, 2018;Deinlein et al, 2017;Ferrarotto, 2017;Lipson et al, 2016;Ravulapati et al, 2017;Stevenson et al, 2017;Tran et al, 2017;Winkler et al, 2017;Zalaudek et al, 2019), excluding the ongoing trials in Phase I and II (Licitra et al, 2017;Kudchadkar et al, 2018;Maubec et al, 2019). Although the larger number of reported cases, responses data are not enough and in addition with short period of follow-up.…”
Section: Pembrolizumabmentioning
confidence: 99%
“…In their case, the patient showed complete response after only two cycles and after six cycles the patient was still progression free. Subsequently, Assam et al () (level of evidence [LE] 4 following Oxford CEBM Levels of Evidence) showed a case of complete response after two cycles of treatment and the maintenance of free of disease recurrence for 12 months. The latter underlined for the first time the importance of the mutational burden, evidencing the mutation in MLH1 and in the DNA miss match repair.…”
Section: Introductionmentioning
confidence: 99%
“…In a preclinical mouse model, PD-1-PDL-1 activation contributed to the development of cSCC [6]. Moreover, the efficacy of anti-PD-1 mAb in patients with cSCC has been reported recently in a few case series [7][8][9][10][11][12][13][14][15][16][17] and in a Phase 1-2 trial with cemiplimab [18]. Herein, we report for the first time two complete responses (CR), allowing treatment discontinuation without recurrence to date, in a series of four patients with advanced cSCC treated with pembrolizumab and concurrent hypofractionated radiotherapy.…”
mentioning
confidence: 99%